Measuring treatment burden related to general practice in patients with multimorbidity: development and validation of a PROM - Per Kallestrup; Anne Frølich; Susanne Reventlow; Volkert Siersma; Anne Møller; Janus Laust Thomsen; Tora Grauers Willadsen; Jesper Bo Nielsen; Line Bjørnskov Pedersen; Henrik Larsen; Anne Holm; Anders Prior; et al. (Family Medicine and Community Health)
Introduction This study aimed to either identify or develop and validate a patient-reported outcome measure (PROM) to assess treatment burden related to general practice for patients with multimorbidity, which can be used alongside the MultiMorbidity Questionnaire part 1 (MMQ1) without overwhelming the target population with redundant items.Methods We conducted a systematic literature review to identify all existing PROMs measuring treatment burden. If no suitable PROM was found, our plan was to: (1) develop a draft PROM using items from existing instruments, (2) carry out group and individual interviews with patients with multimorbidity to ensure the PROM’s understandability, clarity, completeness and relevance and (3) undertake psychometric validation with a diverse sample of primary care patients with chronic conditions.Results We did not identify an eligible PROM in the literature review. The draft PROM consisted of 30 items divided into six domains; Information about treatment, Challenges with medication, Medical appointments, Self-monitoring, Health behaviour and Challenges in the contact to the health system. In the psychometric validation, neither these domains nor any other theoretical constellation of items had adequate psychometric properties. Individual items had good criterion validity and sensitivity to change.Conclusions In this study, we developed a 30-item PROM with high content validity where various individual items showed adequate criterion validity and sensitivity to change, making these items useful as a supplemental measure to the MMQ1.Trial registration number NCT05676541 Registration Date: 16 December 2022.